Metallic impurity content behavior during ICRH-heated L-mode discharges in EAST. (22nd September 2020) - Urbanczyk, G.; Zhang, X.J.; Zhang, L.; Colas, L.; Dumont, R.; Tierens, W.; Lerche, E.; Van Eester, D.; Heuraux, S.; Yang, X.D.; Qin, C.M.; Ekedahl, A.; et al.
Abstract: This study uses the diversity of materials at known locations in the experimental advanced superconducting tokamak to extract, local information on which plasma-surface interaction processes are dominant during ion cyclotron resonance heating (ICRH) (near vs far field effects). Metallic impurity content is indicated by the intensity of impurity line emissions observed with a fast-time-response extreme ultraviolet spectrometer, normalized to line-averaged plasma density, i.e. I imp / n e . Parametric dependencies are explored over scans of ICRH and LH (lower hybrid) power and for different toroidal phasings between straps, strap power balance, and magnetic configurations. This diversity of behavior is interpreted as the signature of different physical processes. Before 2017, as only the upper divertor region contained tungsten (W), the W content in the core used to increase a lot when moving from lower to upper single null configurations, and was correlated with the total injected power rather than the ICRH power. Molybdenum, covering the part of the inner wall facing one ion cyclotron range of frequencies (ICRF) antenna appear sensitive to this antenna power and phasing benchmarked by modeling suggesting a probable interaction due to residual ICRF waves crossing the plasma. Materials close and magnetically-connected to an active antenna show better correlation with ICRF antenna electrical tuning than those which are far away, or not connected. This is particularly the case with W since 2018, because the limiter tiles of the LH launchers were changed from graphite to tungsten. In these latter conditions, it is shown that W sources at the mid-plane (equatorial plane) contribute to a significant fraction of the core contamination by tungsten (25% in ohmic regime, and more during ICRH).